1998
DOI: 10.1016/s0741-5214(98)70201-0
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of calf vein thrombosis: Lysis of thrombi and development of reflux

Abstract: Isolated calf vein DVT leads to few early complications (ie, clot propagation, pulmonary emboli) and few adverse sequelae at 3 years. The peroneal vein is most commonly involved and should be a part of the routine screening for DVT. Lysis of clot usually occurs by 3 months. Although valvular reflux rarely is found in the affected calf vein at 3 years, reflux may be found in adjacent uninvolved veins in approximately 30% of the cases. The question of whether this will lead to future sequelae, such as ulceration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 16 publications
6
95
1
1
Order By: Relevance
“…11,27) Previous investigations have indicated that isolated calf DVTs have better prognosis, with a relatively lower incidence of complications of proximal propagation (3%-32% of cases 10,[13][14][15]24,27,28,29) ) and PE (2%-21% of cases 10,11,[13][14][15]30) ). However, an epidemiological study revealed that the prognosis of patients with bilateral distal DVT is as poor as that of patients with bilateral proximal DVT in terms of mortality and the recurrence rate of DVT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,27) Previous investigations have indicated that isolated calf DVTs have better prognosis, with a relatively lower incidence of complications of proximal propagation (3%-32% of cases 10,[13][14][15]24,27,28,29) ) and PE (2%-21% of cases 10,11,[13][14][15]30) ). However, an epidemiological study revealed that the prognosis of patients with bilateral distal DVT is as poor as that of patients with bilateral proximal DVT in terms of mortality and the recurrence rate of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…9, No. 1; 2016; pp [15][16][17][18][19][20][21] Online December 11, 2015 ©2016 Annals of Vascular Diseases doi:10.3400/avd.oa. who had pre-fatal examinations or any treatment for VTE were excluded from this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of isolated calf vein thrombosis, particularly with respect to development of postthrombotic syndrome, remains controversial, opinions ranging from few adverse sequelae, such as mild to moderate venous valvular insufficiency mostly in segments not involved with the calf thrombosis [39,40], to more severe problems with PE, persistent symptoms and development of valvular incompetence in approximately one quarter of the patients [41].…”
Section: Calf-vein Thrombosismentioning
confidence: 99%
“…But even in nonpregnant women, proximal propagation of deep vein thrombosis from the calves into the popliteal or thigh veins can vary and can be less than 5%. 7 The natural course of distal or proximal deep vein thrombosis in pregnancy is even less known.…”
mentioning
confidence: 99%